СЕРУМ ФЕТУИН-А И НИВОИ РАНКЛА КОД ПАЦИЈЕНАТА СА РАНИМ СТАДИЈОМ РАКА ДОЈКЕ: SERUM FETUIN-A AND RANKL LEVELS IN EARLY STAGE BREAST CANCER - usul afşar, çiğdem; aral, hale; can, orçun; can trablus, didem; karaçetin, didem; nazlı, mehmet ali; gürsu, Rıza umar; karabulut, senem (Journal of Medical Biochemistry, 2022)
Purpose:Breast cancer (BC) is the primary cause of mortality due to cancer in females around the world. Fetuin-A is known to increase metastases over signals and peroxisomes related with growing. Receptor activator of nuclear factor-κB ligand (RANKL) takes part in cell adhesion, and RANKL inhibition is used in the management of cancer. We aimed to examine the relationship between serum fetuin-A, RANKL levels, other laboratory parameters and clinical findings in women diagnosed with early stage BC, in our population. Methods:Women having early stage BC (n=117) met our study inclusion criteria as they had no any anti-cancer therapy before. Thirty-seven healthy women controls were also confirmed with breast examination and ultrasonography and/or mammography according to their ages. Serum samples were stored at -80°C and analysed via ELISA. Results:Median age of the patients was 53 (range: 57-86) while it was 47 (range: 23-74) in the healthy group. Patients had lower high-density lipoprotein levels (p=0.002) and higher neutrophil counts (p=0.014). Fetuin-A and RANKL levels did not differ between the groups (p=0.116 and p=0.439, respectively) but RANKL leves were found to be lower in the favorable histological subtypes (p=0.04). Conclusion:In this study, we found no correlation between serum fetuin-A levels and clinical findings in patients diagnosed with early stage BC. However, RANKL levels are found to be lower in subgroups with favorable histopathologic subtypes such as tubular, papillary and mucinous BC and there was statistically significant difference.